Tungsten melting and erosion under plasma heat load in tokamak discharges with disruptions. (August 2017) - Budaev, V.P.; Martynenko, Yu.V.; Grashin, S.A.; Giniyatulin, R.N.; Arkhipov, I.I.; Karpov, A.V.; Savrukhin, P.V.; Shestakov, E.A.; Solomatin, R.Yu.; Begrambekov, L.B.; Belova, N.E.; Fedorovich, S.D.; et al.
Highlights: Tungsten poloidal and mushroom limiters were tested in tokamak plasma discharges with disruptions. Significant melting and formation of small craters and erosion of the tungsten limiter have been observed. Theoretical description of the tungsten erosion in tokamak assuming no vapor shielding layer is proposed. Abstract: Full tungsten poloidal and mushroom limiters were tested in series of experiments with disruptions in the T-10 tokamak. Significant melting, formation of small craters and erosion of the tungsten limiter have been observed after ∼400 discharges with disruption. A theoretical description of the tungsten erosion at disruption in tokamak plasma is presented. The proposed model was verified by comparison with experimental observations in the T-10. The results are used for the erosion prediction of the ITER tungsten divertor.